Perceptions of the ’Proper Family’ in Palestinian-Arab Society in Israel as Reflected in Family Members’ Drawings - Meler, Tal; Marnin-Distelfeld, Shahar (Journal of Ethnic and Cultural Studies, 2023)
Family lives in Palestinian-Arab society in Israel have undergone considerable changes in recent decades. These changes have made it difficult to understand what is meant by family in everyday life. The aim of the present study is to examine the differences in the perception of the family and the image of “a proper family” through drawings created by Palestinian-Arab women and men in Israel (n=106). This can be analyzed as a prism of discussion regarding how people identify what is expected of families. It also raises the question of “family boundaries” in contemporary Palestinian-Arab society in Israel and what is recognized as family relationships. The drawings’ analysis included a set of questions regarding both the content—the theme of the drawing, main situations, characters, and symbols—and the forms, composition, and colors used. Reading the drawings visually illuminated various perceptions of a family as expressed by the participants. This visual content analysis enhances sociological comprehension about the desirable family life in light of gender relationships, family size, and domestic everyday practices which negotiate the global and the local.